The impact of decisions of Mining Industrialists Congresses on the Industrial Revolution increasing in Ukraine in the late XIX century - Gutnyk, Maryna; Radohuz, Serhii (Державний університет інфраструктури та технологій, 2020)
The activity of the mining industry in the South of the Russian Empire, of which Ukraine was part at that time, is analyzed. It is noted that the rapid development of industry in the Russian Empire after the abolition of serfdom in 1861 opened up opportunities for investors to raise capital. Information is given about why Kharkiv became the center of investment life of mine owners, namely its good geographical location. Data on the number of inhabitants of the city and the number of trading institutions are provided. The stages in the formation of the mining industry of the South of the Russian Empire as a driving force for economic development in Ukraine are highlighted.The causes of weak coal sales from the Donbas and the development of the factory industry of Ukraine in the 1860s are analyzed. It is shown how these issues were resolved. In particular, mining congresses were organized to discuss and resolve these issues.It is shown how the decisions of mining congresses influenced the development of the country's economy at the end of the nineteenth century. Examples of issues discussed at these congresses are given. In particular, the congresses discussed – workers, higher and secondary specialized education, mining credit, insurance, the ratio of the mining industry to zemstvos and land taxation of enterprises of the mining industry, taxes, land relations, postal, telegraph and telephone traffic, passenger traffic in the Southern Russia area, duties, ports, marinas, navigable rivers and canals, shipbuilding and merchant shipping, export of mineral fuel abroad, construction of new railways, etc. It should be noted that the central issue discussed at almost all mining congresses was the question of tariffs, and this was not a coincidence, since it directly concerned the markets for industrialists without whom production could not be developed, and with it the intensification of the industrial revolution. Therefore, this problem, in one form or another, has arisen constantly.Information is provided on the number of such congresses, as well as on the creation of a permanent body, the Council of Miners of the South of the Russian Empire. It analyzes the so-called “coal crisis” and the role of major mining companies in the collusion. The monopolization of the market is considered. Emphasis is placed on the customs policy of the tsarist government. Speculation on temporary fuel difficulties is illustrated. It is noted that at the end of the 1890s, there were especially high rates of development of the Donbas coal industry. Special tariffs for the export of Donetsk coal abroad were introduced. Thus, in the last quarter of the 19th century, the mining and monopolization of the mining industry of the south of the Russian Empire were enlarged and monopolized.

Аналізується діяльність гірничопромисловців півдня Російської імперії, частиною якої на той час була Україна. Наголошується, що бурхливий розвиток промисловості Російської імперії після скасування кріпацтва у 1861 р. відкрив можливості інвесторам для збільшення капіталу. Подано відомості про те чому саме Харків став центром інвестиційного життя гірничопромисловців. Надані дані про чисельність мешканців міста та кількість закладів торгівлі. Виокремлено етапи у формуванні гірничопромисловців Півдня Російської імперії як рушійної сили розвитку економіки в Україні. Показані причини слабкого збуту вугілля з Донбасу та розвиток фабрично-заводської промисловості України у 1860-ті. Показано, яким чином було вирішено ці проблеми. Зокрема, вказано, що саме для обговорення та вирішення цих питань було організовано з’їзди гірничопромисловців. Встановлено, яким чином рішення з’їздів гірничопромисловців впливали на розвиток економіки країни наприкінці ХІХ ст. Наведено приклади питань, що обговорювалися на цих з’їздах. Серед них: робітники, вища і середня спеціальна освіта, гірничопромисловий кредит, страхування, відношення гірничої промисловості до земств і земського оподаткування підприємств гірничозаводської промисловості, податки, земельні відносини, поштово-телеграфне і телефонне повідомлення і пасажирський рух у районі рудників і заводів півдня Росії, мита, порти, пристані, судноплавні річки і канали, суднобудування і торговельне мореплавство, експорт мінерального палива за кордон, будівництво нових залізниць і т.д. Треба зазначити, що питання тарифів обговорювалося практично на всіх гірничопромислових з'їздах. Це було не випадково, адже воно безпосередньо стосувалося ринків збуту для промисловців, без яких не могло розвиватися виробництво, а з ним й інтенсифікація промислової революції. Тому ця проблема, в тій чи іншій формі, виникала постійно. Подано інформацію про кількість таких з’їздів, а також створення постійно діючого органу – Ради з’їздів гірничопромисловців півдня Російської імперії. Здійснено аналіз так званої "вугільної кризи" та роль великих гірничопромисловців у зговорі. Розглянуто монополізацію ринку. Акцентується увага на митній політиці царського уряду, спекуляціях на тимчасових паливних труднощах. Наголошується, що на кінець 1890-х років припали особливо високі темпи вугільної промисловості Донбасу. Було запроваджено спеціальні тарифи для вивезення донецького вугілля за кордон. Таким чином в останні чверті ХІХ ст. відбулося укрупнення та монополізація гірничо-видобувальної галузі півдня Російської імперії.
Вплив рішень з’їздів гірничопромисловців на розгортання промислової революції в Україні у другій чверті ХІХ ст.
Keywords: mining congresses; South of the Russian Empire; coal; tariffs; exchange committees; південь Російської імперії; вугілля; тарифи; біржові комітети